Environment Security for Traditional Craft Villages in Bac Ninh Province (Vietnam) - Thang, A.P Dr. Le Van; Hai Thanh, Dr. Nguyen; Van Tuan, Dr. Nguyen (American Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
Production and business activities in traditional craft villages leave a great impact on the security of their living environment. This study focuses on analysing environmental security of traditional craft villages in Bac Ninh province (Vietnam) to identify the environmental reality of this area, assess the environment impact on people and their attitudes on this issue. Data were collected from 350 households surveyed in 7 communes having wellknown traditional handicraft villages of Bac Ninh province, from local authorities and observation results of Bac Ninh People’s Committee from 2011 to 2016. Based on surveyed reaility, the author has made some recommendations to local authorities in ensuring environmental security for traditional craft villages in Bac Ninh (Vietnam) for the near future.